Автономний глузд як джерело конфліктів та чинник оповсякденення - Карівець, Ігор (Видавництво Львівської політехніки, 2011)
Проаналізовано функціонування автономного глузду та шляхи його приходу до абсолютної влади над усіма сферами людського життя. Крім цього, розглянуто можливість синтезу розуму, глузду та чуттів у феномені sensus communis як такого, що виводить людину у трансперсональну та надособистісну площину. In this article the author analyzes the functioning of autonomous common sense and considers common sense’ ways of dominance over all domains of human life. In addition to this, the author considers the possibility of new synthesis of reason, autonomous common sense and senses in the phenomenon of sensus communis, which helps human being to enter transpersonal and superpersonal sphere.
The autonomous common sense as the source of conflicts and everydayness
Keywords: автономний глузд; інтенціональність; розум; синтез; філософія глузду; autonomous common sense; common sense; intentionality; reason; philosophy of common sense; sensus communis; synthesis